Freezing effect on brain density in postmortem CT. (January 2016) - Sugimoto, Miyu; Hyodoh, Hideki; Rokukawa, Masumi; Kanazawa, Ayumi; Murakami, Rina; Shimizu, Junya; Okazaki, Shunichiro; Mizuo, Keisuke; Watanabe, Satoshi
Highlights: Two deteriorated cadavers were evaluated whole body by postmortem CT and full autopsy. Prior to examination, dry ice was used to prevent worm invasion and minimize deterioration of cadaver. Postmortem brain CT demonstrated lower density at the dry-iced side, and the freezing effect (sherbet like parenchyma) was confirmed by autopsy. The sherbet tissue showed relatively lower CT value than normal organ, and the postmortem condition should be evaluated to prevent misdiagnosis. Abstract: Two 60-year-old males were found at their homes whose bodies had deteriorated due to putrefaction. To prevent worm invasion and minimize deterioration, dry ice was used prior to the autopsy investigation. Prior to autopsy, postmortem CT demonstrated a decreased density in brain parenchyma at the dry-iced side, and autopsy revealed deteriorated brain parenchyma with frozen effect (presented like sherbet). Moreover, the deteriorated cerebral parenchyma maintained their structure and they were evaluated by cutting. When lower CT density presents in postmortem CT, the freezing effect may need to be considered and the physician should evaluate the cadaver's postmortem condition to prevent misdiagnoses.